Comparative metabolic profiling of olive leaf extracts from twelve different cultivars collected in both fruiting and flowering seasons - Kabbash, Eman M.; Abdel-Shakour, Zeinab T.; El-Ahmady, Sherweit H.; Wink, Michael; Ayoub, Iriny (Scientific reports, 2023)
Olea europaea is an economically significant crop native to Mediterranean countries. Its leaves exhibit several biological properties associated to their chemical composition. The aqueous ethanolic extracts of olive leaves from twelve different cultivars were analyzed by high performance liquid chromatography coupled to photodiode array and electrospray ionization mass spectrometry (HPLC/PDA/ESI-MS/MS). A total of 49 phytochemicals were identified in both positive and negative ionization modes. The identified compounds belonged to four classes of secondary metabolites including secoiridoids, flavonoids, pentacyclic triterpenoids and various phenolic compounds. Seasonal variation in chemical composition among the studied cultivars was apparent in autumn and spring. Secologanoside, oleuropein, hydroxy-oleuropein, demethyl oleuropein, gallocatechin, luteolin-O-hexoside, diosmetin, oleanolic acid and maslinic acid were detected in all cultivars in both seasons. Oleuropein-O-deoxyhexoside was tentatively identified for the first time in olive leaf extracts; detected only in the Spanish cultivar Picual (PIC) collected in spring. Also, dihydroxy-oxooleanenoic acid and hydroxy-oxooleanenoic acid, two bioactive pentacyclic triterpenes, were identified. Principle component analysis (PCA) showed good discrimination among the studied cultivars in terms of their botanical origin. This study is considered the first study for non-targeted metabolic profiling of different olive leaf cultivars cultivated in Egypt.